2013
DOI: 10.1021/ja406500h
|View full text |Cite
|
Sign up to set email alerts
|

A C–C Bonded Phenoxyl Radical Dimer with a Zero Bond Dissociation Free Energy

Abstract: The 2,6-di-tert-butyl-4-methoxy-phenoxyl radical is shown to dimerize in solution and in the solid state. The X-ray crystal structure for the dimer, the first for a para-coupled phenoxyl radical, reveals a bond length of 1.6055(23) Å for the 4-4’ C–C bond. This is significantly longer than typical C–C bonds. Solution equilibrium studies using both optical and IR spectroscopies show that the Keq for dissociation is 1.3 ± 0.2 M at 20 °C, indicating a C–C bond dissociation free energy of −0.15 ± 0.1 kcal mol−1. V… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
38
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(42 citation statements)
references
References 38 publications
3
38
1
Order By: Relevance
“…The non‐benzenoid central ring is illustrated by the C−C ring bond distances, featuring four shorter and two longer bonds. The C−O bond length [1.255(2) Å] is consistent with the length of the same bond in other phenoxyl radical crystal structures . The molecular packing of 1 is shown in Figure S1 (Supporting Information).…”
Section: Methodssupporting
confidence: 78%
See 1 more Smart Citation
“…The non‐benzenoid central ring is illustrated by the C−C ring bond distances, featuring four shorter and two longer bonds. The C−O bond length [1.255(2) Å] is consistent with the length of the same bond in other phenoxyl radical crystal structures . The molecular packing of 1 is shown in Figure S1 (Supporting Information).…”
Section: Methodssupporting
confidence: 78%
“…Solution EPR studies of galvinoxyl radical at different temperatures have revealed behavior consistent with dimerization; however, the nature of the diamagnetic species is unclear . In 2013, Mayer and co‐workers reported the X‐ray crystal structure and dissociation thermochemistry of a 2,6‐di‐ tert ‐butyl‐4‐methoxyphenoxyl radical dimer (the dimerization is thermally reversible in solution), which revealed the occurrence of a long and very weak C−C sigma bond . Recently, some of us have reported the synthesis of an unusually stable phenoxyl radical 2,6‐bis‐(8‐quinolylamino)‐4‐( tert ‐butyl)phenoxyl baqp 1 .…”
Section: Methodsmentioning
confidence: 99%
“…3). 31 As found for 12 , Δ H 298d of 6.1(5) kcal mol –1 is outbalanced by T Δ S 298d = 6.3 kcal mol –1 (298 K). We find a similar enthalpy–entropy compensation for t Bu- 1 2 with Δ H 298d = 7.94(3) kcal mol –1 and T Δ S 298d = 9.5(3) kcal mol –1 (298 K); this compares well with other weakly bonded hydrocarbons ( cf.…”
mentioning
confidence: 69%
“…It was recently shown experimentally that the 2,6‐di‐ tert ‐butyl‐4‐metoxyphenoxyl radical dimerises in solution and in the solid state (reaction a). In the same study, a bond dissociation Gibbs free energy around zero (−0.2 ± 0.1 kcal/mol) was measured leading to a Δ E value of 17 ± 2 kcal/mol.…”
Section: Applicationsmentioning
confidence: 99%